Endoscopic Versus Histological Disease Extent at Presentation of Paediatric Inflammatory Bowel Disease. Issue 2 (February 2016) - Ashton, James J.; Coelho, Tracy; Ennis, Sarah; Vadgama, Bhumita; Batra, Akshay; Afzal, Nadeem A.; Beattie, R. Mark
ABSTRACT: Objectives: The Paris classification (PC) of paediatric inflammatory bowel disease categorises disease extent and therefore affects treatment decisions. Histological (microscopic) disease extent is not incorporated, and endoscopic (macroscopic) findings may underrepresent disease extent when compared with histological findings; this study compares disease extent at presentation. Methods: Data were obtained of patients <17 years of age diagnosed with inflammatory bowel disease from 2010 to 2013 at University Hospital Southampton. Data are presented as percentage of patients undergoing endoscopy. PC was performed alongside a modified PC by histological disease location. Results: A total of 172 patients were identified (median age at diagnosis 13.5 years, 115 boys); Crohn disease (CD) 107, ulcerative colitis (UC) 50, inflammatory bowel disease unclassified (IBDU) 15; 159 had undergone upper gastrointestinal (GI) endoscopy, 163 had undergone lower GI endoscopy. Histological disease was more extensive at all points for CD, UC, and IBDU. CD—endoscopic ileal disease in 49% of patients compared with histological disease in 71.3%. Comparing PC—a 10% increase in L3 disease (ileocolonic), a 24% increase in L3 + L4a disease (ileocolonic plus upper GI), and a 27% increase in all of the upper GI involvement if histological disease extent was used. UC—the most common disease location was the rectum (endoscopic 91.5% vs histological 93.6%) and descending colon (endoscopic 89.4% vs histological 95.7%). Comparing PC—a 19% increase in E4 disease (pancolitis) if histological disease extent was used. Conclusions: These data confirm that histological disease extent is greater than endoscopic disease extent. This should be considered when the PC is used. Further study is needed to elucidate which classification would better predict disease outcome.